Improving Pervious Concrete Pavements for Achieving More Sustainable Urban Roads. (2016) - Bonicelli, Alessandra; Arguelles, Gilberto Martínez; Pumarejo, Luis Guillermo Fuentes
Abstract: Pervious concrete is a novel pavement material characterized by a porous structure that allows the water to percolate through it with consequent numerous environmental benefits. However, high-drainability characteristics do not generally correspond to high strength and good surface conditions when submitted to vehicular traffic, hence, to date, the applications of pervious concrete are limited to particular urban areas. In addition, mix design and rigorous construction standards have not yet been defined. The present laboratory study aimed to compare the properties of several pervious concrete mixtures submitted to different compaction energies. The main objectives were, on one hand, to define the effects of compaction energy on the design requirements of strength and drainability, on the other, to compare the reinforcing effect of different admixtures on the material properties. Different percentages of sand and several reinforcing fibres with various physical and chemical properties were added to the mixes, changing water to cement ratio while fixing the aggregate size distribution and the paste content. Laboratory tests, such as indirect tensile strength, elastic modulus, and Cantabro resistance, were conducted to measure the mechanical behaviour of the material; while, porosity, bulk density and drainability capacity were evaluated to define volumetric and functional characteristics. The result of this investigation provided useful information about the effectiveness of laboratory compaction to achieve the optimal strength-drainability balance, adequate for the different urban uses. Moreover, this study identified the suitable admixtures, with the appropriate proportioning, that could enhance the mechanical properties of the material leading to a wiser use in medium-high traffic roads.